Fabrication and characteristic study of alumina tool using cold isotatic press - Adam, Abdul Aziz (2014)
In manufacturing, machining is widely used in the production. The selection of a suitable tool will boost production performance and reduce costs. In this study, alumina cutting tools are fabricated and its characteristics information gained through various experiments. Numbers of previous studies using alumina -based composite cutting tool were done and mostly agreed that the alumina based have the potential to produce a homogeneous ceramic cutting inserts with high performance. However, less research were found for the production of alumina milling cutting insert. Therefore, this study focuses on the application of cold isostatic press to produce alumina cutting insert that has a good microstructure and mechanical properties. The characteristic of cutting insert that has been produced then tested through various experiments and test. The inserts produce accordance to triangle shaped inserts. Alumina powder with purity of 91.4 % was used to produce the cutting tool. The powder then compressed through cold isostatic pressure techniques. The pressure applied is range of 15,000 psi, 20,000psi and 25,000 psi. Green body and then dried and sintered at two different temperatures of and 1400 °C and 1550 °C. The density, hardness and shrinkage of alumina milling insert then were studied. Matrix design method was utilized to build experimental and accurate data. Product which were pressed at 20,000 psi and sintered at 1550 °C shows assured result and shall be tested to identify the cutting performance of the inserts.